PENGARUH APLIKASI PUPUK POLYHALITE DAN KCl TERHADAP KADAR K DAN PERTUMBUHAN BIBIT TANAMAN JERUK PAMELO (Citrus maxima) DI KEBUN PERCOBAAN BALITJESTRO, BATU - Retno Suntari; S Sutopo; Aryo Gilang Maudyansa (Jurnal Tanah dan Sumberdaya Lahan, 2020)
There are still many farmers in Indonesia who use a single fertilizer such as N, P, or K fertilizer. While the needs of plant nutrients are not only that nutrients but also other macronutrients. One of single fertilizer used is KCl fertilizer which only contains essential K nutrients and micro Cl nutrient elements. To overcome this problem, another source of K fertilizer that does not contain Cl is used, especially in Pamelo citrus nurseries. POLY4 fertilizer is used as a source of K nutrients, because it has an excess of containing several nutrients such as K (14%), Ca (17%), Mg (6%), and S (19%). This research was conducted at the BALITJESTRO screen house and the Soil Department Laboratory, Faculty of Agriculture, Brawijaya University. The research design used was a completely randomized design with 5 treatments i.e P0 (100% MOP), P1 (50% POLY4 + 50% MOP), P2 (100% POLY4), P3 (150% POLY4), and P4 (200% POLY4). Parameters of this research were plant height, numbers of leaf, soil pH and exchangeable K, and K content in plant. Result of this study indicated that application of 50% POLY4 + 50% MOP (642 kg ha-1 POLY4 + 150 kg ha-1 MOP) significantly affected the height and number of leaves of Pamelo orange seedlings in 12 weeks, respectively 6.39% and 13.6 % compared to 100% MOP/control (300 kg ha-1 MOP). Application of 150% POLY4 (1,927 kg ha-1 POLY4) significantly increased plant K level by 9.40% compared to control (300 kg ha-1 MOP). Application of POLY4 fertilizer had no significant effect on pH and exchangeable K. The best dose of fertilizer in Pamelo citrus nurseries is the application of POLY4 642 kg ha-1 POLY4 + 150 kg ha-1 MOP (50% POLY4 + 50% MOP).